A biotechnologist's dream: 'doubly green' processes. Issue 6 (11th July 2017) - Segura, Ana
Abstract : Biosurfactants have not fulfilled the expectations generated when they were initially discovered. Heavy vacuum gas oil (HVGO) is conventionally treated with costly thermo‐chemical processes and cause environmental pollution. What if we could bio‐upgrade this HVGO at the same time that we produce a fine chemical?